Arhitektura v ravnovesju - Marolt, Peter (AR. Arhitektura, raziskave, 2004)
Based on the hypothesis that universal order exists in world order, the article attempts to establish ties between cosmic order and architecture as a "cosmic art". It points out the system of the art of spatial design, which copies the arch-pattern (logic) of cosmic order. Logical spatial order represents the arch-pattern and model for operation of all entities that create it. From facts about ways, in which to order the world, we can deduce the thesis that interdependent, polarised elements of (complex) pairs, also apply to architecture. By concluding from general to particular and particular to general, mainly by analogy, the basic premise that architecture is art, science and philosophy can help in equating a system of pairs and simultaneously prove that good architecture relies on a sum of (inter)dependent balanced pairs, which creatively support each other. Thus we indirectly prove that art and artistic-spatial composition are those elements ,without which there is no art of spatial design - architecture.
Keywords: architecture; arhitektura; oblikovanje prostora; kozmos; teorija; theory